Cultural, Educational and Charitable Activities of Immigrant Communities in North Caucasus (Second Half of XIX - Early XX Centuries) - B. V. Tuaeva; E. I. Kobakhidze (Научный диалог)
The article is devoted to the formation of a multi-ethnic and multicultural environment of North Caucasian cities and settlements in the second half of the XIX - early XX centuries, where a significant place was given to ethnic communities of European migrants. On the example of the life of the German, Greek, and Polish communities, we consider the features of the development and support of educational, enlightenment, social, and cultural initiatives. The authors of the article revealed that all social initiatives and practices in the North Caucasus were correlated with reforms and sociocultural policies in the country as a whole, and also served as an example of the effectiveness of ongoing activities to involve the region in the all-Russian space. It is emphasized that through voluntary non-governmental associations the poor were supported, targeted assistance was provided to those in need. It is proved that educational projects, which contributed to the dissemination of scientific knowledge and familiarization with European and Russian culture, were particularly relevant in the diverse activities of societies (charitable, ethno-confessional, cultural, educational, artistic, scientific). It is concluded that it was the Russian language as the state-forming, communication and progressive factor in the development of society that acted as an integration and adaptive resource in the multi-ethnic and multi-confessional North Caucasus region.